Structural Characterization of Gracilariopsis lemaneiformis Polysaccharide and Its Property in Delaying Cellular Senescence - Wang, Xiaomei; Xu, Xiaogang; Mao, Genxiang; Guo, Yue; Wang, Guangce; Sun, Xue; Xu, Nianjun; Zhang, Zhongshan (Frontiers in Nutrition, 2022)
The sulfated polysaccharide was isolated from the purified G. lemaneiformis polysaccharide (PGP), and its property in delaying H2O2-induced 2BS cellular senescence was studied. The results showed that PGP was a linear polysaccharide containing alternating α-(1 → 3)- and β-(1 → 4)-galactopyranose units. Most of the sulfate groups are at C6 of the -(1 → 4)-α-D-Galp, and a small part of them are at C3 and C6. PGP pretreatment could decrease SA-β-gal-positive cells and prevent the formation of senescence-associated heterochromatic foci (SAHF) induced by H2O2 in a dose-dependent manner. It is speculated that PGP may delay aging by downregulating the expression of p21 and p53 genes. The finding provides new insights into the beneficial role of G. lemaneiformis polysaccharide (GP) on retarding senescence process.